2014
DOI: 10.12691/jfnr-2-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Energy Drinks Consumption amongst Medical Students and Interns from Three Colleges in Jeddah, Saudi Arabia

Abstract: Background: Consumption of energy drink represents an escalating global public health problem especially among adolescents and young adults. Energy drink contains stimulants mainly caffeine that marketed as mental and physical stimulator although there are many safety concerns against use. Objectives: To determine the prevalence, pattern and predictors of energy drink consumption among medical students and interns in medical colleges, Jeddah, Saudi Arabia. Materials and methods: A cross-sectional study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 22 publications
5
16
0
8
Order By: Relevance
“…(22) Most of this study's participants declared that they consume energy drinks to help them stay awake, study, and feel energetic. These mentioned reasons for using energy drinks were also mentioned by young adults who participated in similar studies that were conducted in Saudi Arabia, (3,25,38) Lebanon, (17) the United States, (2) Poland, (24) Zambia, (22) and Taiwan. (23) Interestingly, less than 5 % of the students who participated in this study reported mixing energy drinks with drugs or alcohol.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…(22) Most of this study's participants declared that they consume energy drinks to help them stay awake, study, and feel energetic. These mentioned reasons for using energy drinks were also mentioned by young adults who participated in similar studies that were conducted in Saudi Arabia, (3,25,38) Lebanon, (17) the United States, (2) Poland, (24) Zambia, (22) and Taiwan. (23) Interestingly, less than 5 % of the students who participated in this study reported mixing energy drinks with drugs or alcohol.…”
Section: Discussionmentioning
confidence: 86%
“…It was found in various studies that young people knew energy drinks have side effects and experienced some of them, yet they still consumed them for various reasons. (2,17,(24)(25)(26)33,38) Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
“…The smoking habit also seemed to be associated with energetic drinks consumption (Ibrahim et al, 2014) in adolescents and young in South-Arabia. The culture in which young people is immersed can also be a factor related to the smoking habit.…”
Section: Introductionmentioning
confidence: 95%
“…When it comes to university population, it is observable how this gap has been investigated in relation with the identification of their physical activity habits (Blasco, Cruz, Pintanet i Bassets, Capdevila, & Valiente, 1996), smoking habits (Hasim, 2000), creation of smoking habits (Rozi, Butt, & Akhtar, 2007), relation between the consumption of energetic drinks and smoking habits (Ibrahim et at., 2014), drugs consumption (Molina et al, 2012), nutritional habits (Marcondelli, Costa, & Schmitz, 2008;Sakamai, Toyama, Amamoto, Lui, & Shinfuky, 2005;Yahia, Achkar, Abdallah, & Rizk, 2008), energetic food and physical inactivity (Hall, Ochoa, & Muñiz, 2014), unhealthy nutritional habits (Silliman, Rodas-Fortier, & Neyman, 2004;Younis, 2014), and the time invested in physical activity (Silliman et al, 2004). In Spain, a total of 720 undergraduates from Galicia completed a questionnaire whose results showed that 78.3% of the students consume alcohol, 31.7%, tobacco and 34% has consumed illegal drugs at any time.…”
Section: Introductionmentioning
confidence: 99%
“…Energy drinks (ED) are beverages that contain stimulant compounds such as caffeine and sugar, in addition to other ingredients such as vitamin-B, amino acids, and herbal stimulants 1 . Most ED have caffeine content of as much as 35–160 mg (highly caffeinated as per the EU definition) 2 and 37 g (equivalent to almost nine teaspoons) of processed sugar per 8-ounce serving 3 .…”
Section: Introductionmentioning
confidence: 99%